2‐Keto‐3‐Deoxy‐l‐Rhamnonate Aldolase (YfaU) as Catalyst in Aldol Additions of Pyruvate to Amino Aldehyde Derivatives. Issue 12 (19th May 2017) - Hernández, Karel; Gómez, Ariadna; Joglar, Jesús; Bujons, Jordi; Parella, Teodor; Clapés, Pere
Abstract: 4‐Hydroxy‐2‐keto acid derivatives are versatile building blocks for the synthesis of amino acids, hydroxy carboxylic acids and chiral aldehydes. Pyruvate aldolases are privileged catalysts for a straightforward access to this class of keto acid compounds. In this work, a Class II pyruvate aldolase from Escherichia coli K‐12, 2‐keto‐3‐deoxy‐l ‐rhamnonate aldolase (YfaU), was evaluated for the synthesis of amino acid derivatives of proline, pipecolic acid, and pyrrolizidine‐3‐carboxylic acid. The aldol addition of pyruvate to N ‐protected amino aldehydes was the key enzymatic aldol addition step followed by catalytic intramolecular reductive amination. The corresponding N ‐Cbz‐amino‐4‐hydroxy‐2‐keto acid (Cbz=benzyloxycarbonyl) precursors were obtained in 51–95% isolated yields and enantioselectivity ratios from 26:74 to 95:5, with chiral α‐substituted N ‐Cbz‐amino aldehydes. ( S )‐ N ‐Cbz‐amino aldehydes gave aldol adducts with preferentially ( R )‐configuration at the newly formed stereocenter, whereas the contrary is true for ( R )‐ N ‐Cbz‐amino aldehydes. Addition reactions to achiral amino aldehydes rendered racemic aldol adducts. Molecular models of the pre‐reaction ternary complexes YfaU‐pyruvate enolate‐acceptor aldehyde were constructed to explain the observed stereochemical outcome of the reactions. Catalytic reductive amination of the aldol adducts yielded 4‐hydroxy‐2‐pipecolic acid, and unprecedented C‐5 substituted 4‐hydroxyproline and pyrrolizidine‐3‐carboxylic acid derivatives. Abstract :